Archive zwischen Konflikt und Kooperation / Arkiver mellem konflikt og samarbejde. 75 Jahre deutsch-dänisches Archivabkommen von 1933 / 75 år dansk-tysk arkivoverenskomst af 1933 - Hering, Rainer (Veröffentlichungen des Landesarchivs Schleswig-Holstein, 2008)
With this publication, the Landesarchiv Schleswig-Holstein and the Danish State Archives celebrate the 75th anniversary of the signing of the German-Danish Archives Agreement. As is already a tradition in German-Danish archival cooperation, this is done in German and Danish. All texts of the publication are therefore available in both languages.The former archivist Hans Kargaard Thomsen, Copenhagen, wrote a detailed report in the 1990s entitled "Arkivoverenskomsten med Tyskland 1933 og dens forhistorie" ("The Archives Agreement with Germany of 1933 and its Prehistory"). It forms the core of the publication. This is followed by guidelines on the use of archival material exchanged in 1936 under the agreement between Germany and Denmark. The archivists Malte Bischoff, Landesarchiv Schleswig-Holstein, and Hans Schultz Hansen, Landsarkivet for Sønderjylland, are the authors of these texts. The annex contains the wording of the German-Danish archive agreement.